The Black Sea Region Energy Cooperation: Current Trends and Prospects - Bakulina, Anna A.; Panina, Olga V.; Prokofiev, Stanislav E.; Krasyukova, Natalia L.; Abramov, Valery L.; Sergeeva, Natalia V.; Loseva, Olga V.; Kasyanenko, Tatiana G.; Takmakova, Elena V. (International Journal of Energy Economics and Policy, 2021)
The Black Sea region is one of the most complex regions in terms of energy development. It hosts several major powers and some developing countries that need to cut energy costs. In general, the region is controversial. It is influenced by external actors, and therefore regional stability is very difficult to achieve. In addition, institutional players such as the EU, the Belt and Road Initiative, the Black Sea Trade and Development Bank, etc., have their own vision of the future of the Black Sea region. The article is aimed at assessing the regional balance of power and estimating the interests of the countries of the region. Based on this assessment, the authors have classified the countries in the region, predicted potential alliances, and provided recommendations on how the countries should behave in the region. The key findings comprise the rejection of the two hypotheses: the countries of the region cooperate mainly through similar institutions; and the countries of the region can efficiently cooperate within the framework of a single strategy. The novelty of the article is in a new look on the regional distribution of power and new strategies for cooperation between countries in the region. Keywords: The Black Sea region, energy sector, strategy, institutions, balance of power JEL Classifications: F59, Q48 DOI: https://doi.org/10.32479/ijeep.11247